A Rhetoric of Cooperation: How Swedish parties argued in parliament 2015 and 2016 after the migration agreement - Rebecca Kiderlen (Res Rhetorica, 2023)
The aim of this topos analysis is to identify features of argumentation in Swedish parliamentary debates on asylum policy in 2015 and 2016 compared to German debates. Findings include a focus on procedural rather than substantive aspects and an adaptation of government-like argumentation by cooperating opposition parties. These can be attributed to the focus on consensus and cooperation in Sweden, governed by a minority government, and may be typical of minority governments, common in Scandinavia, in general.